A Generalization of Pratt-Arrow Measure to Nonexpected-Utility Preferences and Inseparable Probability and Utility - Nau, Robert F. (Management Science, 2003)
The Pratt-Arrow measure of local risk aversion is generalized for the n-dimensional state-preference model of choice under uncertainty in which the decision maker may have inseparable subjective probabilities and utilities, unobservable stochastic prior wealth, and/or smooth nonexpected-utility preferences. Local risk aversion is measured by the matrix of derivatives of the decision maker's risk-neutral probabilities, without reference to true subjective probabilities or riskless wealth positions, and comparative risk aversion is measured without requiring agreement on true probabilities. Risk-neutral probabilities and their derivatives are shown to be sufficient statistics for approximately optimal investment and financing decisions in complete markets for contingent claims.